HYPERTENSIVE PATIENT RECORD MOBILE APPLICATION - Farah Izzati, Abu Bakar (Universiti Malaysia Sarawak (UNIMAS), 2020)
Hypertensive is one of the most common disease we hear in our daily lives. It often occurs from different range of ages. Therefore, people with hypertensive disease should always record their blood pressure readings to monitor their readings to avoid high risk. Mobile applications are very popular today. These apps help us greatly in our daily lives. So, we need to take this opportunity to use mobile applications to make our life easier. Since many people use mobile applications nowadays, this proposed application which is Hypertensive Patient Record Mobile Application is focused on hypertensive patients to make them easier to record their blood pressure reading. It helps them to record blood pressure reading more easily and can view the reading whenever and wherever without interrupted.